I’m Not Sure We Had A Choice?: Decision Quality and The Use of Cardiac Implantable Electronic Devices In Older Adults With Cognitive Impairment - Fowler, Nicole R.; Shaaban, C. Elizabeth; Torke, Alexia M.; Lane, Kathleen A.; Saba, Samir; Barnato, Amber E. (Cardiology and Cardiovascular Medicine, 2018)
Background: The decision to implant a cardiac device in a person with Alzheimer’s disease or related dementia requires considering the possible trade-offs of quality of life (QOL) and quantity of life. This study measured the decision-making experience of patients with and without cognitive impairment (CI) who received a cardiac device and their family members who were involved in the decision. Methods and Results: Semi-structured interviews and questionnaires were administered with 15 patient-family member dyads. Interviews revealed few conversations between physicians, patients and family members about the patient’s cognitive status or about the benefits, risks, and long-term implications of the device for someone with CI. Participants largely stated that the decision to get the device was based on the patient’s functional status at the time of the implant, and not on expectations about future functioning. Patients with CI had more regret, measured with the Decision Regret Scale (DRS), (p=0.037) and family members of patients without CI reported more decisional conflict, measured with the Decisional Conflict Scale (p=0.057). Conclusions: Although CI impacts life expectancy and QOL, cognitive status was largely not discussed prior to device implant. Few differences were found between the experiences of dyads that included patients with or without CI.